دراسة مقارنة بين ذوي القلق والخوف العالي والواطئ في بعض القدرات النفسية واالجتماعية واآلداء الفني للسباحة الحرة - . Thaibt Ibrahim, Dureid Majeed Hameed Yaseen Al-Hamadani Suleman (Mustansiriyah Journal of Sports Science, 2024)
This study was applied to a sample of the students of the college of Physical Education and Sports Science at the University of Anbar For the academic year 2018-2019 the study aimed identify the differences in the movement performance of swimming among those with special anxiety and fear of water and to learn high and low swimming for the sample of the study. The researcher used the descriptive and experimental approaches to suit the nature and problem of the study. And he used the two lists of the scale of personal attitudes and beliefs towards swimming and water with a rate of(23) items for each list. After collecting the data and statistically processing them, the following conclusions were reache-The movement performance of students with anxiety and low fear of water and learning swim better than those with anxiety and high fear. Through the results that appeared, the researcher recommended the following recommendations: -The necessity of opening educational swimming courses for students in the (primary, intermediate and preparatory) schools, and removing anxiety and for due to negative thoughts and beliefs towards the water and learning to s